DETERMINANTS OF TAX COMPLIANCE IN SURABAYA : A STUDY OF COGNITION, VOLITION AND TAX AVOIDANCE - Rodhiyah Rodhiyah (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2026)
The research raises critical concerns regarding the declining tax realization and widespread tax avoidance, resulting in substantial revenue losses for the state. Additionally, it underscores the need for improved tax policy implementation and greater societal awareness to address these issues and enhance taxpayer compliance, ultimately optimizing regional or state revenues from the tax sector. This research aimed to analyze the influence of socialization, information technology, attitudes, knowledge and abilities on Taxpayer Compliance with awareness, volition as intervening, and tax avoidance as moderation on individual taxpayers in the city of Surabaya. This research employs an explanatory design. The population for this study consists of individual taxpayers registered with the KPP East Java Region I, totaling 3,042,548 people in 2020. A sample of 400 respondents was chosen using the Slovin formula to represent this population. Data analysis was conducted using Smart PLS. We found that socialization positively influenced taxpayer awareness, negatively impacted volition and taxpayer compliance. Information technology had mixed effects, showing insignificant influence on some factors. Attitude significantly affected awareness and volition but had an insignificant influence on compliance. Knowledge strongly influenced awareness, volition, and taxpayer compliance. The ability to pay taxes had a positive impact on awareness, volition, and taxpayer compliance. Additionally, awareness and volition had mixed influences on taxpayer compliance when moderated by tax avoidance. These findings confirm or contradict previous research regarding taxpayer behavior and compliance.